Synthesis, electronic and emission spectroscopy of diphenylamine-azulene co-oligomers - Merkhatuly, Nurlan; Iskanderov, Ablaykhan; Abeuova, Saltanat; Iskanderov, Amantay; Kadirberlina, Gulpan; Seitkan, Ainur; Kemelbekova, Arailym (Chemical Bulletin of Kazakh National University, 2025)
New strategies for creating functional materials are of great interest for the further development of optoelectronic devices such as organic field-effect transistors (OFETs), organic light emitting diodes (OLEDs), dye-sensitized organic solar cells (DSSCs) and others. In this area, research has focused on the application of various building blocks that can fine-tune the electronic structure of materials to optimize the fabrication performance and morphology. To date, the most effective molecules as building block are aromatic hydrocarbons, for example azulenes. In this study, new conjugated diphenylamine-azulene co-oligomers with linear and branched structures were synthesized with high yields via the Suzuki–Miyaura cross-coupling reaction. The obtained co-oligomers exhibit a pronounced ability to absorb and emit visible light in the 400–700 nm range. It was demonstrated that these unique photophysical properties, particularly the intense emissions in the green and orange photoluminescence range, result from the electron-donating properties of diphenylamine groups and the expansion of π-conjugation, which significantly alters the electronic structure of azulene, including the levels and energy gaps of the frontier HOMO-LUMO orbitals. These findings provide a rational approach to designing a series of new conjugated co-oligomers based on diphenylamine-azulenes for optoelectronic and photonic devices.